Extension of the a-Si:H electronic transport model to μc-Si:H: use of the μ0τ0 product to correlate electronic transport properties and solar cell performances - Goerlitzer, M.; Torres, Pedro; Droz, C.; Shah, Arvind (My University, 2000)
The aim of this communication is to show that it is possible to extend the model of the electronic transport developed for amorphous silicon (a-Si:H) to microcrystalline silicon (μc-Si:H). By describing the electronic transport with the μ0τR products (mobility×recombination time) as a function of the Fermi level, we observed the same behaviour for both materials, indicating a similar type of recombination. Moreover, applying the normalised μ0τ0 product (mobility×life-time) obtained by combining the photoconductivity (σphoto) and the ambipolar diffusion length (Lamb) measured in individual layers, we are able, as in the case of a-Si:H, to predict the quality of the solar cells incorporating these layers as the active < i > layer.
Keywords: microcrystalline silicon; photoconductivity; ambipolar diffusion length